2022
DOI: 10.3390/ijerph19159485
|View full text |Cite
|
Sign up to set email alerts
|

Household Groups’ Land Use Decisions Investigation Based on Perspective of Livelihood Heterogeneity in Sichuan Province, China

Abstract: Land use decision-making is a vital livelihood strategy associated with the rational collocation of livelihood asset endowments by rural households. Based on the perspective of livelihood heterogeneity, this paper collected the data from 540 farm households in 27 villages in three Sichuan Province counties to identify the land use decision-making characteristics of the household groups. A land use decision-making framework (LUDF) based on the sustainable livelihood framework (SLF) was established and dynamic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Nonetheless, II PTRH did not increase its investment in agricultural production due to the non-agricultural employment of family members. The extant literature supports this view that non-agricultural employment reduced the input of labor, capital, and other factors per unit of land, causing a change in the original intensive farming pattern [ 49 , 50 ]. On the one hand, this result may arise from non-agricultural income being mainly used for non-productive expenditures, such as improving the livelihood of rural households and purchasing durable goods [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, II PTRH did not increase its investment in agricultural production due to the non-agricultural employment of family members. The extant literature supports this view that non-agricultural employment reduced the input of labor, capital, and other factors per unit of land, causing a change in the original intensive farming pattern [ 49 , 50 ]. On the one hand, this result may arise from non-agricultural income being mainly used for non-productive expenditures, such as improving the livelihood of rural households and purchasing durable goods [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some scholars have studied the relationship between livelihood capital and adaptive decision-making, and found that natural capital, social capital, human capital and physical capital will promote farm households to adopt climate change adaptation decisions, while financial capital will hinder farm households to adopt climate change adaptation strategies (Kuang et al, 2019). In addition, some scholars have studied the relationship between livelihood capital and land use decisions, and found that the diversity of livelihood capital has little impact on farm households' land transfer decisions, and the stock of livelihood capital will affect farm households' land transfer-in and self-cultivation (Tang et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By reviewing the existing relevant literature, it is found that there is a large space to expand the research on the impact of livelihood capital and information capacity on farm households' tourism livelihood. First, most of the existing studies study the role of livelihood capital on farm households' livelihood decision-making from a linear perspective (He and Ahmed, 2022;Huang et al, 2021;Kuang et al, 2019;Tang et al, 2022). However, from the perspective of non-linear livelihood capital arrangement, there are few studies on the portfolio utility of livelihood capital to its livelihood decision making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, academic research on the effects of HSFC is mainly interested in the economic effects of promoting grain production [ 11 , 12 ], increasing farmers’ income [ 13 ], the social profitability of driving regional development [ 14 ], and reducing carbon emissions [ 15 ]. As for the factors influencing farmland transfer, existing research has mainly focused on property rights [ 16 , 17 , 18 ], agricultural socialized services [ 19 ], human capital [ 20 ], social capital [ 21 ], and fragmentation [ 22 ]. In 2022, Chen and Hong conducted a study exploring the impact of HSFC on farmland transfer with Jiangxi Province as the sample [ 23 ].…”
Section: Introductionmentioning
confidence: 99%